2021
DOI: 10.1016/j.imr.2021.100729
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic device developed for non-invasive moxibustion therapy

Abstract: Background Recently, some adverse effects of moxibustion has been reported such as burns, smoke, allergies, and so on. To overcome the adverse effects of traditional moxibustion, an ultrasonic moxibustion device (UMD) was designed, simulated, fabricated, and tested. The objective of this study is to provide detailed information about the main design parameters, simulation outcome, and performance-test results. Methods The main components of the UMD are a 1-MHz ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…The series of moxibustion therapies involves many techniques, such as moxa stick moxibustion, moxa cone moxibustion, direct moxibustion, and indirect moxibustion. Moreover, many distinctive complex moxibustion manipulations are organically combined, such as partitioned moxibustion, moxa-moxibustion, and warm moxibustion [12] . Studies that combine moxibustion with other therapies, such as acupuncture, massage, drugs, and physical interventions, will be included if they can prove that moxibustion is effective.…”
Section: Methodsmentioning
confidence: 99%
“…The series of moxibustion therapies involves many techniques, such as moxa stick moxibustion, moxa cone moxibustion, direct moxibustion, and indirect moxibustion. Moreover, many distinctive complex moxibustion manipulations are organically combined, such as partitioned moxibustion, moxa-moxibustion, and warm moxibustion [12] . Studies that combine moxibustion with other therapies, such as acupuncture, massage, drugs, and physical interventions, will be included if they can prove that moxibustion is effective.…”
Section: Methodsmentioning
confidence: 99%
“…A aplicação da moxabustão na pele pode ser efetuada por métodos indireto ou direto (KIM et al, 2021). No método indireto, colocam-se materiais entre a pele e a moxa, podendo ser utilizado gengibre, alho, sal ou o próprio ar para favorecer a resposta terapêutica (SILVA FILHO, 2020).…”
Section: Introductionunclassified
“…O sangue também chamado de Xue é definido como uma das substâncias vitais, que complementa a ação nutriente do Qi e flui para todo o organismo (SCHWARTZ, 2008). Um meridiano é um canal que percorre por debaixo da superfície da pele e por A emissão de ondas de radiação de longa duração da moxabustão (KIM et al, 2021;PACH;BRINKHAUS;WILLICH, 2009) afeta os tecidos melhorando a função celular e a circulação sanguínea (GUAITA, 2021;WIDMER et al, 2007). A moxabustão age a partir da fumaça, das ervas e dos efeitos biofísicos no potencial infravermelho (HUANG et al, 2016).…”
Section: Introductionunclassified
“…[9] At the present stage, moxibustion has been proven to participate in the treatment of COVID-19 as an auxiliary means and has achieved good results. [10,11] But, there is no high-quality evidence on moxibustion for diarrhea in COVID-19. Therefore, we designed this study to better understand the effectiveness and safety of moxibustion therapy for diarrhea in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that moxibustion can reduce serum inflammatory factors and improve intestinal dysfunction in a rat model of diarrhea [9] . At the present stage, moxibustion has been proven to participate in the treatment of COVID-19 as an auxiliary means and has achieved good results [10,11] . But, there is no high-quality evidence on moxibustion for diarrhea in COVID-19.…”
Section: Introductionmentioning
confidence: 99%